Produksi Dan Kualitas Melon (Cucumis melo L.) Pada Konsentrasi Dan Waktu Pemberian Pupuk Mono Kalium Phospate (MKP) - Prayuda, Galih Dwi; Ali, Fahri; Erfa, Lisa; Kartina, Raida; Sesanti, Rizka Novi (Politeknik Negeri Lampung, 2024)
Potassium is really needed by melon plants to increase the sweet taste of the fruit. The element potassium can improve the size and quality of fruit during the plant's generative period and can add a sweet taste to the fruit. Meanwhile, phosphorus functions in the process of forming plant flowers and fruit as well as increasing fruit production and ripening. The aims of the research were to study interaction between the concentration and time application of MKP fertilizer on the production and quality of melon (Cucumis melo L.) and the effect of concentration and time application of MKP fertilization on the production and quality of melon (Cucumis melo L.). This experiment used Randomized Complete Block Design, which consist 2 factors, first factor was concentration of MKP fertilizer. Second factor was time application of MKP fertilizer. Data obtained were analyzed with F test, and were continued with HSD at 5 percent when significant. Results showed that there is an interaction between the concentration of MKP fertilizer and the time of application of MKP fertilizer for melon production and quality on the parameters of fruit weight, fruit diameter and total soluble solids. Providing MKP fertilizer with a concentration of 9 g.l-1 and application time of MKP fertilizer 42 and 49 days after planting is a good combination for melon production and quality in the parameters of fruit weight (3.16 kg), fruit diameter (13.65 cm), and total dissolved solids (13.73 °brix). Providing MKP fertilizer with a concentration of 9 g.l-1 is the best fertilizer concentration for melon production and quality in the parameters of fruit weight (3.16 kg), fruit diameter (13.65 cm), and total soluble solids (13.73 °brix). MKP fertilizer application time of 42 and 49 HST is the best time for melon production and quality in the parameters of fruit weight (3.16 kg), fruit diameter (13.65 cm), and total soluble solids (13.73 °brix).